Congenital Absence of the Patellar Tendon: A Report of 2 Cases. Issue 2 (April 2021) - Haws, Brittany E.; Sanders, James O.; Cook, P. Christopher
Abstract : Case: Isolated unilateral congenital patellar tendon absence is a rare condition that has not been well described. We report on 2 patients with congenital patellar tendon absence that underwent soft-tissue reconstruction of their patellar tendon. We present the clinical and radiographic features, surgical management with both single-stage and multistage approaches, and postoperative outcomes for the treatment of this condition. Conclusion: Soft-tissue reconstruction of the patellar tendon led to satisfactory outcomes, providing active knee extension and improved ambulation in both cases. In cases of significant superior migration, multiple procedures may be required to mobilize the patella to an appropriate position.